EFFECT of DIFFERENT AIRBORNE-PARTICLE ABRASION/BONDING AGENT COMBINATIONS on THE BOND STRENGTH of A RESIN CEMENT TO A BASE METAL ALLOY - Fonseca, Renata Garcia [UNESP]; Martins, Samira Branco; Abi-Rached, Filipe de Oliveira [UNESP]; dos Santos Cruz, Carlos Alberto [UNESP] (Mosby-elsevier, 2012)
Statement of problem. Investigation of surface treatments to improve the bond of resin cements to metals may contribute to the longevity of metal ceramic restorations.Purpose. The purpose of this study was to evaluate the efficacy of surface treatments on the shear bond strength (SBS) of a resin cement to nickel-chromium (NiCr) alloy.Material and methods. Eighty cast NiCr alloy disks (9 x 3 mm) were divided into 8 groups (n=10), which received 1 of the following surface treatments: 1) 50 mu m Al2O3 particles + silane; 2) 120 mu m Al2O3 + silane; 3) 30 mu m silica-modified Al2O3 (Cojet Sand) + silane; 4) 120 mu m Al2O3 followed by 110 mu m silica-modified Al2O3 (Rocatec) + silane; 5) 50 mu m Al2O3 + metal primer; 6) 120 mu m Al2O3 + metal primer; 7) 30 mu m silica-modified Al2O3 (Cojet Sand) + metal primer; and 8) 120 mu m Al2O3 followed by 110 mu m silica-modified Al2O3 (Rocatec) + metal primer. The silane was RelyX Ceramic Primer and the metal primer Alloy Primer. RelyX ARC resin cement was bonded to NiCr alloy surfaces. Specimens were thermally cycled before shear mode testing. Data (MPa) were analyzed by 1-way ANOVA and the Tukey test (alpha=.05). Failure mode was determined with a stereomicroscope (x20).Results. The results revealed that surface treatment was significant (P<.001). There was no significant difference between 50 mu m and 120 mu m Al2O3 particles, regardless of the bonding agent used (silane or metal primer). Cojet Sand provided lower SBS than Rocatec, both in the groups treated with silane (P<.001) and metal primer (P<.01). No significant difference was observed between silane and metal primer in the groups abraded with 50 mu m and 120 mu m Al2O3 particles. Metal primer decreased the SBS of both Cojet Sand and Rocatec groups (P<.001). Rocatec + silane had the highest SBS and Cojet Sand + metal primer the lowest. All groups presented 100% adhesive failure.Conclusions. Particle size influenced SBS only in the groups abraded with silica-modified Al2O3. The bonding agent did not affect SBS in the groups abraded with Al2O3. Alloy Primer was not chemically compatible with silica-modified Al2O3. Both mechanical (particle size) and chemical (silica/silane interaction) factors contributed to the high SBS of Rocatec + silane. (J Prosthet Dent 2012;108:316-323)